Bandwidth extension method based on nonlinear audio characteristics classification - Li-yan ZHANG; Chang-chun BAO; Xin LIU; Xing-tao ZHANG (Tongxin xuebao)
A bandwidth extension method based on audio classification was proposed.Time series of audio signals were classified into four types based on recurrence plot and recurrence quantification analysis,and the fine spectrums were recovered by taking advantage of four methods respectively.In addition,the spectrum envelope and energy gain were adjusted by Gaussian mixture model and codebook mapping on the basis of soft decision respectively.Subjective and objective testing results indicate that the proposed method has good quality compared with conventional blind bandwidth extension methods,and the performance of ITU-T G.722.1 codec with the proposed algorithm is better than that of G.722.1C codec at the same bit rate.